2016
DOI: 10.1136/bcr-2016-217418
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive arachnoiditis in mixed connective tissue disease: a rare neurological manifestation

Abstract: The overall incidence of neurological manifestations is relatively low among patients with mixed connective tissue disease (MCTD). We recently encountered a case of autoimmune adhesive arachnoiditis in a young woman with 7 years history of MCTD who presented with severe back pain and myeloradiculopathic symptoms of lower limbs. To the best of our knowledge, adhesive arachnoiditis in an MCTD patient has never been previously reported. We report here this rare case, with the clinical picture and supportive ancil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 19 publications
0
13
1
1
Order By: Relevance
“…The spinal cord lesions from the pugs with thoracolumbar myelopathy in this study shared many features with the spinal cord of laboratory dogs, used in research about adhesive, also called constrictive, arachnoiditis . Adhesive arachnoiditis, a rare chronic myelopathy in people, is characterized by meningeal fibrosis that has been described to cause disruption of the vascular supply and the development of arachnoid diverticula, syringomyelia and myelomalacia . Familiar adhesive arachnoiditis, with a suggested genetic influence, has been described .…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The spinal cord lesions from the pugs with thoracolumbar myelopathy in this study shared many features with the spinal cord of laboratory dogs, used in research about adhesive, also called constrictive, arachnoiditis . Adhesive arachnoiditis, a rare chronic myelopathy in people, is characterized by meningeal fibrosis that has been described to cause disruption of the vascular supply and the development of arachnoid diverticula, syringomyelia and myelomalacia . Familiar adhesive arachnoiditis, with a suggested genetic influence, has been described .…”
Section: Discussioncontrasting
confidence: 38%
“…39,40 Adhesive arachnoiditis, a rare chronic myelopathy in people, is characterized by meningeal fibrosis that has been described to cause disruption of the vascular supply and the development of arachnoid diverticula, syringomyelia and myelomalacia. [41][42][43][44][45][46] Familiar adhesive arachnoiditis, with a suggested genetic influence, has been described. [47][48][49] In process dysplasias, are difficult to document without CT. 3 Although a previous study, including pugs of similar age as in the present study, could not confirm an association between CVMs and neurological signs, it has been suggested that some CVMs in pugs are indeed clinically significant.…”
Section: Macroscopic Findingsmentioning
confidence: 99%
“…The female ‐to‐male ratio is 9:1, and no significant geographical distribution of the disease has been noted . Ten percent of MCTD patients have reported trigeminal neuropathy .…”
Section: Mixed Connective Tissue Diseasementioning
confidence: 99%
“…Trigeminal neuralgia‐like pain and isolated trigeminal sensory neuropathy have been reported in MCTD, with features suggestive of SS . Sudden pain and numbness have been reported as one of the first manifestations of MCTD presenting unilateral or bilaterally and have variable prognosis . Neurovascular headache is also a relatively common comorbidity .…”
Section: Mixed Connective Tissue Diseasementioning
confidence: 99%
“…En los senos venosos, sobre todo el superior, su reabsorción tiene lugar en forma pasiva, dependiente del gradiente de presión del espacio subaracnoideo y de los propios senos (diferencial de presión de 5-7 mmHg 5 . La aracnoiditis basal es un proceso inflamatorio meníngeo y del espacio subaracnoideo que produce engrosamiento de éstos, así como adhesiones de la duramadre que causan complicaciones, entre ellas aracnoiditis adhesiva, neuropatías, mielopatías y radiculopatías 6 .…”
Section: Introductionunclassified